A Rare Case of Restrictive Cardiomyopathy Presenting With Large, Recurrent Pericardial Effusions. (November 2021) - Cordova Sanchez, Andres; Nealy, Zachariah; Azhar, Atika; Banerjee, Sanchari; Bisen, Maneesh; Kozman, Hani
The association between large pericardial effusion and restrictive cardiomyopathy (RCM) is uncommon and has seldom been described. We describe an uncommon case of a 31-year-old male with RCM who presented with large, recurrent pericardial effusion, heart failure, and echocardiographic findings showing progressive worsening of diastolic function even after total pericardiectomy who was eventually transferred for cardiac transplant evaluation.